2018
DOI: 10.1007/s00384-018-3098-3
|View full text |Cite
|
Sign up to set email alerts
|

The influence of tumour site on prognosis in metastatic colorectal carcinomas with primary tumour resection

Abstract: In a surgical patient cohort undergoing primary tumour resection, significant differences in prognosis were observed between patients with metastatic right- and left-sided colorectal carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…We recently demonstrated that 30.6% of patients with synchronous metastases of CRC can undergo treatment with curative intent, with an OS of 53.0% at 5 years [ 32 ]. Similarly, Merkel et al investigated the improvement in prognosis over time in a cohort of 937 patients who underwent primary tumor resection from the Erlangen Registry for Colorectal Carcinomas [ 33 ]. They found an increase in 2-year OS from 25.9% to 55.6% for the time periods 1985–1994 compared to 2005–2014.…”
Section: Discussionmentioning
confidence: 99%
“…We recently demonstrated that 30.6% of patients with synchronous metastases of CRC can undergo treatment with curative intent, with an OS of 53.0% at 5 years [ 32 ]. Similarly, Merkel et al investigated the improvement in prognosis over time in a cohort of 937 patients who underwent primary tumor resection from the Erlangen Registry for Colorectal Carcinomas [ 33 ]. They found an increase in 2-year OS from 25.9% to 55.6% for the time periods 1985–1994 compared to 2005–2014.…”
Section: Discussionmentioning
confidence: 99%
“…The cohort featured patients from a broad time frame (1995)(1996)(1997)(1998)(1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010). Primary treatment and therapy of tumor recurrences underwent significant changes at our institution during this period of time: FOLFOX and FOLFIRI chemotherapy regimens were launched from 1995 to 2004, while novel biologic agents, e.g., vascular endothelial growth factor (VEGF) antibodies and epidermal growth factor receptor (EGFR) inhibitors were introduced during 2005 and 2010 [34]. Hence, we included different time periods of surgery into our multivariate regression models to acknowledge the confounding effect of time-related changes.…”
Section: Discussionmentioning
confidence: 99%
“…Primary tumor location is of prognostic importance in metastatic CRC [1,2]. Patients with right-sided disease have a significantly worse prognosis than those with left-sided CRC, independent of treatment [19][20][21][22]. The unfavorable prognosis of rightsided metastatic colon cancer was confirmed in metaanalysis and is universally accepted [1,2,22]; however, a biological explanation for the prognostic value of the location is currently lacking [3].…”
Section: Discussionmentioning
confidence: 99%